Electrocardiogram alterations in pericarditis in children - Peker, Hurşit (The Turkish Journal of Pediatrics, 1963)
The author presents five typical pericarditis cases, and an analysis of the electrocardiograms of 32 pericarditis patients treated at Hacettepe Children's Hospital between the years 1958 and 1961.